Kim and Omberg Revisited: The Duality Approach. (12th August 2015) - Battauz, Anna; De Donno, Marzia; Sbuelz, Alessandro
Abstract : We give an alternative duality-based proof to the solution of the expected utility maximization problem analyzed by Kim and Omberg. In so doing, we also provide an example of incomplete-market optimal investment problem for which the duality approach is conducive to an explicit solution.